Efficacy of antiemetic therapy in patients undergoing laparoscopic cholecystectomy - Llanes Garza, Hilda Alicia; López Cabrera, Norma Guadalupe; Cacho de la Vega, Rosalba; Palacios Ríos, Dionicio; Millán Corrales, Alba Lorena; Pacheco Juárez, M.; Cárdenas Estrada, Eloy (UANL. Facultad de Medicina, 2015)
A high incidence of postoperative nausea and vomiting has been observed in patients undergoing laparoscopic cholecystectomy (20---40%). This causes an increase in patient discomfort, a delay in recovery, and an increase in hospital stay. Objective: Compare the efficacy of ondansetron plus metoclopramide and ondansetron alone in the control of postoperative nausea and vomiting in patients undergoing laparoscopic cholecystectomy. Material and methods: A comparative, prospective, experimental, longitudinal double blind study was performed with 30 patients programmed for laparoscopic cholecystectomy. The Apfel score was applied postoperatively. Patients were divided into two groups with 15 participants. Metoclopramide 10 mg and ondansetron 4 mg were administered in the first Group (A), and ondansetron 4 mg in the second Group (B), after induction of anesthesia. Nausea and vomiting were evaluated for 24 h postoperatively using a Likert scale. Results: Of the patients who presented nausea, the condition was mild. The patient who presented vomiting, vomited only once. Neither group required rescue drugs. Regarding the Apfel score, there was no correlation between the percentage of stratified risk and the patients who presented postoperative nausea and vomiting. Conclusions: No statistically significant difference was observed between ondansetron plus metoclopramide and ondansetron alone in patients subjected to laparoscopic cholecystectomy.